Learning factors of public sector accountants and sharing process of tacit knowledge - Salleh, Kalsom; Syed Ahmad, Syed Noh; Syed Ikhsan, Syed Omar Sharifuddin (2010)
Knowledge Management (KM) implementation in the public sector organization can take advantage the sharing process of experiences, ideas and expertise of its professional intellects for the organization’s embedded knowledge assets.The objective of this paper is to investigate the relationship between the learning factors of professional intellects and the sharing process of tacit knowledge in a public sector accounting organization. A survey questionnaire was used to collect data from all public sector accountants working in the accounting specialist department of the Federal Government in Malaysia. Using factor analysis and multiple regression analysis, the empirical result showed that training and learning opportunities provided to public sector accountants has a high significant impact on the sharing performance of tacit knowledge. It was also found that performance evaluation and incentives together with the ICT skills and know-how are the moderately significant learning factors for an effective leveraging of the public sector accountants for the organizational embedded knowledge assets.